2023
DOI: 10.1007/s00170-023-11838-8
|View full text |Cite
|
Sign up to set email alerts
|

Defect measurement in CFRP drilling based on digital image processing

Abstract: Carbon Fiber Reinforced polymers (CFRPs) are critical kind of materials in many industries due to their superior mechanical and physical properties. However, the pivotal mechanical process of CFRPs is considered to be drilling, which easily leads to CFRPs defects including burr and delamination. Although substantial CFRPs defect inspection methods have been suggested, the user-friendly measurement of CFRPs defects and fast measurement speed are still challenging. To this end, a digital-image-processingbased me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…This can be explained if it is taken into consideration that the cutting speed increases the temperature on the cutting zone, which can in turn soften the epoxy resin, i.e., the matrix of the composite material. This behavior has been found by other authors [ 19 ], although these authors found a lower influence of the cutting speed than that obtained herein, as they worked with a cutting speed range narrower than that under investigation here.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This can be explained if it is taken into consideration that the cutting speed increases the temperature on the cutting zone, which can in turn soften the epoxy resin, i.e., the matrix of the composite material. This behavior has been found by other authors [ 19 ], although these authors found a lower influence of the cutting speed than that obtained herein, as they worked with a cutting speed range narrower than that under investigation here.…”
Section: Resultssupporting
confidence: 86%
“…This can be explained if it is taken into consideration that the cutting speed increases the temperature on the cutting zone, which can in turn soften the epoxy resin, i.e., the matrix of the composite material. This behavior has been found by other authors [19], although these authors found a lower The measured forces in the tests are depicted in Figure 10. It is observed that, among the input parameters, the feed rate and the tool geometry heavily influence the thrust force that appears in the machining process.…”
Section: Cutting Forcessupporting
confidence: 84%
See 1 more Smart Citation